Chromium adsorption on thermally activated adsorbent equipped from waste biomass - Md. Abul Hashem; Julkar Nayeen; Md. Tanvir Hossain; Md. Mukimujjaman Miem (Waste Management Bulletin, 2024)
The emitted wastewater from the tanning industry is extremely catastrophic and that contains a large extent of toxicants including heavy metals, especially chromium (Cr). Its detrimental effect increases due to its higher solubility and mobility in water. In this study, a thermally activated Borassus flabellifer (Palmyra palm) fruit shell was used to assess the removal of Cr from tannery wastewater. The biochar was characterized in terms of FT-IR, SEM micrograph, EDX, and pHpzc. FT-IR analysis represents the functional groups of the biochar, EDX illustrated the presence of elements in biochar, while the SEM micrograph revealed the adsorption through surface morphology. In batch adsorption, an optimum condition for maximum Cr removal was 3-g dose/50 mL wastewater for 10 min stirring time with a relative pH of 7.8. The adsorption mechanism was demonstrated through the pH and pHpzc values. This adsorption technique clarified 84.36 % Cr removal with a significant reduction of COD, Cl-, and BOD 88.07 %, 81.32 %, and 78.77 %, respectively. The relation between adsorbate and adsorbent was assessed by isotherm and kinetic models. The pseudo 2nd-order kinetics equation was well-fitted with a higher regression coefficient (R2 = 0.999). Besides, the Frenudlich model represented a stronger interaction between adsorbent and adsorbate (R2 = 0.9523) than the Langmuir model. Furthermore, this study revealed an innovative approach of utilizing Palmyra palm waste biomass as a thermally activated feasible adsorbent to remove Cr from industrial wastewater.